2023
DOI: 10.1002/jsfa.12464
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of dipeptidyl peptidase‐IV inhibitory peptides from Sacha inchi meal

Abstract: BACKGROUND Sacha inchi meal (SIM) is a by‐product of oil processing. Our previous studies showed that SIM hydrolysates exhibited dipeptidyl peptidase‐IV (DPP‐IV) inhibition activity. The objective of the present work was to identify and characterize the bioactive peptides from protein hydrolysates of SIM; enzyme kinetics and peptide–enzyme interaction were also investigated. RESULTS From SIM hydrolysates, ten peptides responsible for the activity were identified: GPSRGF (GF‐6), FPILSPDPA (FA‐9), APYRRGGKI (AI‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was suggested that an interaction occurred between the three coix seed prolamin-derived inhibitory peptides and DPP-IV. Hydrogen bonding or conjugation occurred between the two, resulting in a wider range of electron activities during the energy jump with the main absorption peaks moving in the long-wave direction . The binding constants K A of 9.16 × 10 3 , 4.50 × 10 4 , and 5.81 × 10 4 mol/L were calculated by fitting the Lineweaver–Burk double inverse curve plot (Figure D) of LPFYPN, TFFPQ, and ATFFPQ interacting with DPP-IV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that an interaction occurred between the three coix seed prolamin-derived inhibitory peptides and DPP-IV. Hydrogen bonding or conjugation occurred between the two, resulting in a wider range of electron activities during the energy jump with the main absorption peaks moving in the long-wave direction . The binding constants K A of 9.16 × 10 3 , 4.50 × 10 4 , and 5.81 × 10 4 mol/L were calculated by fitting the Lineweaver–Burk double inverse curve plot (Figure D) of LPFYPN, TFFPQ, and ATFFPQ interacting with DPP-IV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This assay was performed following the methods described by Zhang et al DPP-IV was diluted to 0.03 U/mL in a Tris–HCl buffer (100 mM, pH 8.0). DPP-IV (1 mL) was gradually added to different concentrations of the peptide solution (Q, 10 μL), and the mixture was equilibrated for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The potent α-glucosidase and α-amylase inhibitory effects are linked to the phenolic content in SI [87][88][89][90]. Furthermore, SI meal-derived peptides demonstrated potent DPP-IV inhibitory activity in vitro, which was further validated with increased glucose consumption by palmitic acid-induced insulin resistant HepG2 cells [91]. It is important to emphasize that α-amylase, α-glucosidase, and DPP-IV inhibitory assays serve as valuable screening tools to evaluate the antidiabetic potential of natural products.…”
Section: Effects Of Si On Glucose Metabolism and Diabetesmentioning
confidence: 86%